Changes to a CA Programme - Practitioners' Perspectives - Elizabeth Wheeler; Mary Low; Grant Samkin (Australasian Accounting, Business and Finance Journal, 2014)
This paper examines the perceptions of practitioners of the new directions taken by NZICA with respect to its academic and professional programme requirements to obtain CA Institute membership. The “future viability of any professional body is dependent on continuously attracting new members, ideally the best and the brightest new tertiary graduates”, and this is “undoubtedly the case for New Zealand’s professional accounting body, the New Zealand Institute of Chartered Accountants (NZICA)” (Malthus & Fowler 2009, p. 26). In this study, the concurrent triangulation approach to mixed methods described by Creswell (2009) was used to collect data. This approach enabled the results of the two quantitative and qualitative databases to be integrated and compared. It was found that accounting practitioners felt the changes made by NZICA may devalue the brand, while the reduction in liberal papers would result in a narrower degree. Overall, accounting practitioners agreed that three to four years of tertiary accounting education was adequate, a broader four-year course would result in a better-rounded graduates. The reduction in the length of the tertiary programme caused concern that future graduates would be less mature. Accounting practitioners also felt that the changes would harm the credibility of NZICA internationally. However, some accounting practitioners did welcome the fact that the NZICA membership requirements will be more aligned with Institute of Chartered Accountants Australia. Accounting practitioners felt that the new technical modules would offer more flexibility. They believed that the four technical modules should repeat the material taught at university, as long as a balance was maintained between technical and practical skills. They also believed that the changes would result in an increased onus on the employer. Additionally, accounting practitioners agreed that on-the-job training should not replace a tertiary qualification in accounting. Accounting practitioners noted that on-the-job training replacing tertiary education meant that individuals who learn better through practical experience would be advantaged. However, if there was no tertiary education, then graduates would face a steep learning curve.
Keywords: Chartered Accountants; Academic and Professional programme; Accounting Tertiary Education; Practitioners' Perspectives